2011
DOI: 10.1111/j.1463-6409.2011.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of a trans‐Wallacean radiation (Squamata, Gekkonidae,Gehyra) supports a single early colonization of Australia

Abstract: Heinicke, M. P., Greenbaum, E., Jackman, T. R. & Bauer, A. M. Phylogeny of a trans‐Wallacean radiation (Squamata, Gekkonidae, Gehyra) supports a single early colonization of Australia. —Zoologica Scripta, 40, 584–602. The genus Gehyra (34 species) is rare among squamate reptile radiations in spanning continents, extending from southeast Asia to Australia and Polynesia. Among the family Gekkonidae sensu stricto, Gehyra is the only genus that is species rich in Australia. We performed molecular phylogenetic, div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 95 publications
3
66
0
Order By: Relevance
“…All new sequences are deposited in GenBank (Appendix 1). Sequences were aligned with and compared to molecular data taken from Sistrom et al (2009) and Heinicke et al (2011). Tamura-Nei genetic divergences (Tamura & Nei 1993) were estimated in MEGA v. 6 (Tamura et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All new sequences are deposited in GenBank (Appendix 1). Sequences were aligned with and compared to molecular data taken from Sistrom et al (2009) and Heinicke et al (2011). Tamura-Nei genetic divergences (Tamura & Nei 1993) were estimated in MEGA v. 6 (Tamura et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast with some other gekkonid radiations occurring in Melanesia (Oliver et al 2012), but like many trans-Wallacean radiations, diversity in this group is asymmetrically distributed -it is most speciose in Australia (Heinicke et al 2011;Doughty et al 2012;Sistrom et al 2013;, with a subsidiary centre of endemism in New Guinea (Oliver et al 2010. The recognized species diversity of Gehyra in East Melanesia and the South-west Pacific is currently low (Zug 2013), with one very widespread form that shows evidence of regionally distinctive subpopulations (Gehyra oceanica (Lesson, 1830)), one moderately sized form from Palau (Gehyra brevipalmata (Peters, 1874)) and two very large species: Gehyra vorax Girard, 1858 from Fiji, and the recently described Gehyra georgepotthaasti Flecks, Schmitz, Böhme, Henkel and Ineich, 2012 from Vanuatu and the Loyalty Islands.…”
Section: Introductionmentioning
confidence: 99%
“…When morphological variation in chromosomes was fi rst investigated in the 1970s and 1980s, researchers found that chromosome types could vary widely within several species, indicating cryptic diversity (King 1979;Moritz 1986). However, recent progress using primarily DNA sequencing has been made towards delimiting species (Horner 2005;Sistrom et al 2009) and placing Gehyra in a global context (Oliver et al 2010b;Heinicke et al 2011). The genetic studies done from tissues of recently collected specimens, in combination with rocky Pilbara region to the south by the Great Sandy Desert .…”
Section: Introductionmentioning
confidence: 99%
“…For morphology, phenotypic expression of colouration can be highly variable and convergent, with patterns fading in preservation leading to the loss of characters. Moreover, the body plan of Gehyra is highly conserved across this old and widespread group, with only subtle changes in shape across widely divergent lineages (Heinicke et al 2011;Ashman et al 2018;Doughty et al 2018;Kealley et al 2018). However, the benefit of working with morphology is that many potentially informative characters can be inexpensively assessed.…”
Section: Discussionmentioning
confidence: 99%